Effectiveness of Educational Intervention Programme on Knowledge Regarding Breast Self Examination Among Higher Secondary School Girls of Biratnagar - Sapkota, D.; Parajuli, P.; Kafle, T.K. (Birat Journal of Health Sciences, 2017)
Introduction Breast self-examination (BSE) is a self-generated, non-invasive and non-irradiative method of breast cancer detection. Self examination of the breasts each month after the menstrual cycle is the simplest yet extremely important way to detect early breast cancer. It has been observed that women can detect 95% of breast cancers and 65% of early minimal breast cancers themselves. This method is harmless, less time consuming and can be performed by any woman.Objective To assess the effectiveness of educational intervention programme regarding Breast Self Examination among girl students of study school.Methodology Pre experimental one group pre-test post-test design was adopted for this study. In total, 61 girls were included. The result were analysed by using both descriptive as well as inferential statistics.Results In pre-test 75.4% had inadequate and only 1.6% had adequate knowledge regarding Breast Self Examination, in contrast, after the intervention the adequate knowledge was increased to 62.3%. The overall mean score was increased from 33.07% to 85.14%. The test of significance revealed that the increment in BSE knowledge score due to program intervention was highly significant (P< 0.001).Conclusion The educational intervention programme on BSE was found to be highly effective as the knowledge score was significantly increased after intervention of the package among higher secondary school girls.Birat Journal of Health Sciences 2016 1(1): 13-19